Bio and nano-engineered anode for high performance microbial fuel cell and its enhancement mechanism - Liu, Jing (2014)
This research focuses on developing novel nanostructured anode materials and engineered bacterial strains to significantly improve the bioelectrocatalytic efficiency and power density of microbial fuel cells (MFCs), and meanwhile exploring the fundamental insights of bacterial electron transfer during the bioelectrocatalytic process. The first approach was to develop a new anode by electrochemically depositing graphene on carbon cloth for a Pseudomonas aeruginosa (P. aeruginosa) mediatorless MFC. The graphene modification improved power density and energy conversion efficiency by 2.7 and 3 times, respectively. To further increase the contact area between bacteria and graphene materials, a novel three-dimensional chitosan/vacuum stripped graphene (CHI/VSG) scaffold with hierarchically porous structure was carefully designed and successfully prepared as anode, which fulfills a remarkable 78 times maximum powder density improvement than carbon cloth anode. Furthermore, a facile bacteria-treatment approach of "perforating" pores and channels on the bacterial membrane was successfully developed to significantly improve the electron transfer rate between bacteria and electrode. In addition, we constructed an arcA knockout mutant Escherichia coli (arcA−) strain which shows enhanced activation of the citric acid cycle for efficient glycerol oxidation under microaerobic condition and excretes an endogenous mediator, resulting in much higher power density than its parental strain. The success of this project advances our knowledge about the electron transfer process and in-depth understanding of the bioelectricity production, and also provides new solutions for future MFCs.